Calculation of Logistics Costs of Implementation Innovative Automatic Identification System in the Warehouse - Kučera, Tomáš (Melandrium, 2019)
Warehousing is the main pillar of the logistic chain. In spite of its importance, issues related to inaccurate item registration, misplacement of goods, and inefficient movement of staff after warehouse remain. Each made error leads to an increase in logistics costs. More and more companies are constantly trying to implement automatic identification system in warehouse management that lead to the solution of these problems at the present time. The most applied automatic identification systems are the use of barcodes and radio frequency identification. The aim of this paper is the implementation of innovative automatic identification system in the warehouse that will lead to the reduction in human error rates when identifying items and increasing work efficiency. The paper is based on the case study, which is one of the qualitative research methods and very useful method in the scientific field. The case study will in detail present two of warehousing cases, which are processing of order for goods warehouse and processing orders for goods removal.
Kalkulace logistických nákladů implementace inovativního automatického identifikačního systému ve skladu
Keywords: calculation of logistics costs, warehousing, automatic identification system; kalkulace logistických nákladů, skladování, automatický identifikační systém